FREQUENCY OPTIMIZATION OF WAVE EXPOSURE AND DOSE TO KILL ultrasonic mosquito larvae - Mansyur, Mas; Rianti, E. Devi Dwi; Setiawan, Heru (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2009)
Mosquito is the one of inflicted insect upon people caused by the lead pard in many indescribable diseases such as malaria, dengue and cikungunya. Mosquito is bring problem for living space especially in decreasing sanitation such flooded area. The disease prevention caused by Mosquito has done in many ways among the others by using insecticide such as DDT, BHC, etc. Insecticide enable to caused poisoned to people and others living creatures. Using uncontrolled insecticide will be give high risk complex. It is a good idea to get a better alternative method. The ultrasonic waves choose as alternative method for its effectiveness and environmental friendliness. The focus of research has been done to have optimum frequency of ultrasonic waves caused highest lethal percentage and to get the dosages or the volume density of energy of ultrasonic waves to destroy Mosquito larva on the whole. As the result of observation and data analysis has done by 50 Mosquito Larva and 50 W ultrasonic powered give the optimum frequency is 86 KHz, with Lethal Percentage is 78%. Besides, is getting the linier relation ship to volume, so that the volume density of energy is 3.95904 kJ/ml.